Clinical and neuroimaging characteristics of diabetic striatopathy: a case series report - Chen, Yaning; Wu, Chunliu; Ren, Ming; Wang, Qingjun; Wang, Zhiwei; Zhang, Yimo; Yu, Yingxin (Frontiers in Endocrinology, 2024)
Background Diabetic striatopathy (DS) is a rare disorder characterized by clinical manifestations of hemichorea, non-ketotic hyperglycemia, and high signal on T1-weighted MRI or high density on CT scan in basal ganglia, typically associated with poor glycemic control. Objective This study aimed to analyze clinical characteristics of patients with diabetic striatopathyto raise awareness amongst physicians, especially endocrinologists, about this rare neurological manifestation in patients with diabetes. Methods We retrospectively analyzed the data on clinical presentations, laboratory workups, and cranial CT and MRI of six patients with DS who were admitted to our hospital from October 2013 to June 2022. Results The mean age of onset among the six patients was 80.5 years, and the mean value of HbA1c was 13.65%. All six patients complained of involuntary movements,which primarily affected the arm and legon one side of the body. Bilateral caudate nucleus hyperdensities were shown on the CT examination in Case 3,while the other 5 patients, unilateral caudate nucleus hyperdensity was shown. In addition, five patients (except Case 5) underwent MRI, all showing hypersignal lesions on the T1-weighted images. A low signal in the right basal ganglia was shown on MRI susceptibility weighted imaging (SWI) sequences in Case 6. All six patients exhibited carotid artery or cerebral artery stenosis. Following strict blood glucose control and symptomatic management, the symptoms of chorea improved significantly in all patients, and repeat images indicated that the lesions gradually disappeared. Conclusion Both poor vascular conditions and severe hyperglycemia contribute to the development of diabetic striatopathy. The prognosis is usually good by active treatment.